Medial patellofemoral ligament reconstruction for patellofemoral instability: a new surgical technique - K. S., Shreekantha; Usman, Mohammed; Malik, Deepak; Aseem, Mahammad; Mulla, Mohammad Gous (International Journal of Research in Orthopaedics, 2021)
The purpose of this study was to present new surgical technique for MPFL reconstruction. We also describe its functional outcome, complications, and the advantages of the procedure. This study is a prospective analysis of collected data during the period of august 2018 to January 2020. Ten cases of patients with recurrent symptomatic patellar instability and who underwent isolated MPFL reconstruction were included in the study. Kujala scoring and lysholm scoring was done to assess the functional outcome at follow-up. Post-operative dislocation and apprehension were recorded in each case along with any complication. Pre-operative Kujala score was 36.80 which improved to 89.80 postoperatively at the time follow-up. Pre-operative lysholm score was 36.80 which improved to 92.70 postoperatively at the time follow-up. The improvement in Kujala score and Lysholm score was found to be highly significant (p<0.01). We have done a simple technique where MPFL is reconstructed anatomically to restore kinematics and stability. Consistent good results with early rehabilitation can be obtained using the described technique.